Agglomeration and regional employment dynamics*. (2nd July 2012) - Dauth, Wolfgang
Abstract In this paper we combine two strands of the empirical literature on agglomeration economics. We calculate two indices to identify local industries where agglomeration externalities could be expected to be particularly strong. The main part of the paper is an econometric analysis using a dynamic panel data model to test whether dynamic employment growth is indeed stronger in these observations. Spatial dependence is taken into account by including spatially lagged exogenous variables. We use panel data on all Western German employees subject to social security from 1989 to 2006 in 326 districts and 191 industries. We find evidence that long run employment growth is significantly more persistent in industrial agglomerations.